PEMANFAATAN TRIGGER TOOL DALAM MONITORING DAN DETEKSI ADVERSE DRUG REACTION PADA PASIEN RAWAT INAP GERIATRI DI RSI PKU MUHAMMADIYAH PEKAJANGAN PEKALONGAN - Prasetya, Henry Budiman; Lolita (Jurnal Insan Farmasi Indonesia, 2024)
The importance monitoring and detection ADR in geriatric inpatients cannot be overstated. Geriatric patients are susceptible to adverse drug effects due physiological changes associated with aging, increased amounts medication consumed, and increased sensitivity drug effects. This study aimed to detect ADR using trigger tools in geriatric inpatients and determine relationship between patient characteristics and incidence ADR. The method used observational with cohort study design retrospective. The samples were all geriatric patients aged ≥ 60 years and who had been hospitalized more than 48 hours period July - September 2023. The instrument used trigger tools from Dutch geriatric guidelines. Analysis using Microsoft Excel 2016 and SPSS 21.0 software. The results detected 393 trigger drug combinations in 34.1% (n = 197/577) patients. Triggers renal insufficiency, hyperglycemia, hyponatremia, hypotension/dizziness, and diarrhea/vomiting accounted for 86.5% (n = 340/393). The overall positive predictive value (PPV) triggers was 49.4%, the majority ADRs were caused by angiotensin receptor blocker (ARB), loop diuretics, NSAIDs, potassium-sparing diuretics, and corticosteroids, which accounted for 69% all drugs involved causing ADR. Analysis relationship shows age factor influences the occurrence ADR. The conclusion shows value trigger drugs as a tool for detecting ADR in inpatient geriatric patients at RSI PKU Muhammadiyah Pekajangan Pekalongan.